Evaluation of Akdag and Cebireis Mountains (Alanya-Antalya) as an Important Plant Area - Bi̇lgi̇li̇, Bilgehan; Duman, Hayri (Kastamonu University, 2015)
Abstract In this study, Akdag and Cebireis mountains were evaluated according to IPA criteria. 11 globally threatened, 108 regionally (European) threatened, 15 nationally rare species and 4 threatened habitats were determined. Also these results were compared with the nearest IPAs. As a result, the research area, located between “Gevne valley and Gokbel plateau” IPA and “Kargi river” IPA, meets IPAs criteria. Consequently, it is suggested that Akdag and Cebireis mountains should be a new IPA or combined with the other two IPAs. Keywords: IPA, Alanya, Turkey
Keywords: IPA; Alanya; Turkey; ÖBA; Alanya; Türkiye; 13. Climate action; 15. Life on land; 6. Clean water